Effectiveness, acceptance and feasibility of home-based intervention model for tuberculosis contact tracing in Kashmir - Khatana, Ghulam Hassan (J Clin Tuberc Other Mycobact Dis, 2019)
BACKGROUND: As long as one case of tuberculosis is replaced by another, elimination of tuberculosis cannot be achieved. Contact tracing is an important strategy for detection of more TB cases early. The present study is concerned with an innovative method of contact tracing. METHODS: A quasi randomized interventional study was conducted in two TB Units of Kashmir for evaluation of newly designed interventional model for its effectiveness, acceptance and feasibility. Data was collected from 1st Jan 2014 to 30th June 2015. RESULTS: In interventional group of 598 eligible household contacts, total 27 (4.51%) contacts were detected as suffering from active pulmonary TB cases. Out these, 21 (3.51%) cases were diagnosed during initial home visit and 6 (1.04%) cases were diagnosed at 6th monthly follow up visit. In controlled group 593 eligible household contacts, total 7 (1.18%) contacts were found suffering from active pulmonary —TB during routine practice under RNTCP for contact screening. In interventional group, during initial home visit by the investigator, 423 (70.74%) of household contacts participated for study and during follow up visit at 6th month, 356 (59.53%) household contacts participated. CONCLUSION: Newly designed “home-based intervention model” for active-case finding among household contacts of index pulmonary-TB case has been found an effective method for contact tracing. This intervention has adequate acceptance by the community and feasible for implementation under existing revised national tuberculosis control programme.